Resistance Detection of Aedes aegypti Larvae To Cypermethrin from Endemic Area In Cimahi City West Java - Endang Puji Astuti; Mara Ipa; Firda Yanuar Pradani (ASPIRATOR - Journal of Vector-borne Disease Studies, 2014)
Abstract. Vector control programs using chemical insecticide e.g organochlorin, organophosphate, carbamate, and pyrethroid (cypermethrin). When those insecticides were applied continuously, it may lead to vector resistance. The aim of this research was to detect any resistance of Ae. aegypti to cypermethrin in endemic areas of Cimahi. This research is a laboratory study that used biochemical test which referred to Lee’s method. Larva samples were collected from 8 villages, which are endemic area. Samples of larvae were collected from 15 villages belonged to dengue endemic areas in town of Cimahi, however, villages that meet the availability of larvae were only 8 villages. To detect the activity of monooxygenase enzyme, a biochemical assay was used in this research by created a reaction between larvae homogenate and sodium acetate substrate. The results of reaction were read using ELISA reader with spectrophotometer wave length of 595 nm. Overall, the results showed that most of the larvae in eight villages of Cimahi is still susceptible to cypermethrin. However, larvae from Cibabat village were 4% resistant, 2% tolerant, and 94% susceptible. On the other hand, Cigugur village showed that 12.7% larvae were tolerant and 87.3% still susceptible. Other villages like Cimahi, Cibeureum, Melong, Baros, Cipageran, and Pasirkaliki still remains susceptible. Resistance detection using biochemical assay of cypermethrin insecticide for Ae.aegypti resulting data stated that in 6 villages were still susceptible but in 3 other villages were already tolerant and 1 village was already resistance.